Composite bone scaffold material for bone tissue repair and preparation method thereof

Through chemical grafting technology, nano-hydroxyapatite is combined with cross-linking network bio-based polyurethane and pore-induced treatment to prepare composite bone scaffolding materials with three-dimensional porous structure and good mechanical properties, which solves the existing bone tissue repair materials The degradation rate is inconsistent with the osteogenesis speed and other problems achieve efficient and safe bone tissue repair.

CN119386279APending Publication Date: 2025-02-07嘉兴南湖学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411528310.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing bone tissue repair materials have problems such as incoordination of the degradation rate and osteogenesis rate, mismatch between mechanical strength and degradation rate, triggering inflammation and immune response, and poor surfactivity, which are difficult to meet the needs of bone tissue engineering.

Method used

Nanohydroxyapatite was compounded with crosslinking network bio-based polyurethane by chemical grafting technology, and through pore-generating treatment, a composite bone scaffold material with a three-dimensional porous structure and good mechanical properties was prepared. The material is degradable in the body and has the effect of promoting wound healing and accelerating collagen tissue deposition.

Benefits of technology

It achieves efficient degradation of bone tissue repair materials and matches good mechanical properties, reduces inflammation and immune response, improves cell adhesion and functional performance, and meets the clinical needs of rapid treatment of bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of bone tissue engineering, and discloses a composite bone scaffold material for bone tissue repair and a preparation method thereof, chitosan and cyclodextrin with good biodegradability participate in polymerization of polyurethane, and L-cysteine is added to terminate the polyurethane, so that the composite bone scaffold material is obtained. The preparation method comprises the following steps: firstly, preparing modified gelatin, then utilizing alkenyl of cyclodextrin in polyurethane and alkenyl of the modified gelatin to initiate polymerization, constructing stable and multifunctional cross-linked network bio-based polyurethane with controllable degradability through a hydrogen bond or a covalent bond and the like, then compounding with hydroxyapatite, and performing pore-forming to play an efficient treatment role in a bone tissue repair process; the cross-linked network bio-based polyurethane has a three-dimensional porous network structure, and the L-cysteine can provide necessary nutritional support, promote proliferation and differentiation of cells, avoid inflammation and accelerate the repair process of tissues, and has a great promotion effect on ingrowth of bones and generation of new bones.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bone tissue engineering, in particular to a composite bone scaffold material for bone tissue repair and a preparation method thereof. Background Art

[0002] Human bone tissue is a dynamic, highly vascularized tissue that can heal itself without leaving scars. Its main function is to provide mechanical and structural support for the human body and protect organs and tissues in the body. Bone defects caused by various reasons such as tumors, infections, congenital malformations, trauma and physical factors all require bone grafting to repair. Currently, allogeneic bone transplantation and autologous bone transplantation are widely used treatment methods in clinical practice, but these methods have certain problems to varying degrees. For example, the source of autologous bone grafts is extremely limited, which increases trauma and cannot be used to repair large bone defects. Allogeneic bone transplantation is also difficult to obtain and has immune rejection reactions. In addition, exogenous bone may carry potential pathogens. Therefore, finding more effective bone tissue repair materials to achieve bone tissue regeneration and reconstruction is the main goal of research in the field of bone repair.

[0003] Bone regeneration and self-repair capabilities are extremely limited, and existing artificial bone prostheses have problems such as insufficient bone repair effect and poor biosafety; artificial bone synthetic materials in the prior art are mostly inorganic materials and polymer organic synthetic materials, among which inorganic materials such as calcium phosphate ceramics and bioactive glass are very good bone tissue engineering scaffold materials, but they have poor plasticity, high brittleness and high preparation conditions, so their application is subject to certain restrictions; polymer organic synthetic materials such as polylactic acid and polyglycolic acid have good biocompatibility, but their acidic metabolites after degradation will reduce the pH value around the polymer, which can cause fibrosis after implantation in the body and cause immune response of surrounding tissues. Biopolymer materials such as collagen, chitosan, gelatin, etc. have good biocompatibility, controllable degradability, mechanical strength, and strong plasticity, and have been widely used in the field of biomedical materials; nanohydroxyapatite has good osteoconductivity and bioactivity, and is similar to the chemical properties of natural bone, and can be used to promote bone repair or new bone formation, but it has many disadvantages, such as mechanical properties that are far from human bones, very low bending strength, and greater brittleness than human bones.

[0004] Therefore, a single type of matrix material has its own advantages and disadvantages. It is difficult to meet the requirements of extracellular matrix materials for bone tissue engineering with only a single material. The problems that need to be solved urgently are: (1) The degradation rate of bone scaffold materials is not coordinated with the osteogenesis rate; (2) The mechanical strength of the material is difficult to match the degradation rate; (3) Some inflammatory reactions and immune reactions will still be caused in the material; (4) The surface activity of the material is poor, which affects the adhesion, distribution and function of seed cells. The present invention combines the characteristics of different materials through chemical grafting, taking advantage of their strengths and making up for their weaknesses, so as to solve the problems existing in bone tissue repair materials in the prior art. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a composite bone scaffold material for bone tissue repair and a preparation method thereof, which has a three-dimensional porous structure and good mechanical properties, is degradable in the body, has the effects of promoting wound healing and accelerating the deposition of collagen tissue, thereby achieving the purpose of rapid treatment of bone defects and meeting clinical needs.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a composite bone scaffold material for bone tissue repair is carried out according to the following steps:

[0008] Step (1), under a nitrogen atmosphere, adding nano-hydroxyapatite and dimethyl sulfoxide into a reaction flask, stirring evenly, adding cross-linked network bio-based polyurethane, reacting at 150-175° C. for 3-8 hours, washing, vacuum filtering, injecting into a mold, maintaining at 8-15 MPa for 5-10 minutes, and drying to obtain a bionic composite material.

[0009] Step (2), adding the bionic composite material, porogen and ethanol into the reaction flask, ultrasonically oscillating, reacting at 60-80°C for 1-3h, pouring into a mold after the viscosity increases, applying pressure at 50-65°C and drying for 16-24h, demolding, cleaning by ultrasonic heating, and drying to obtain a composite bone scaffold material for bone tissue repair.

[0010] Furthermore, in step (1), the mass of the cross-linked network bio-based polyurethane is 2-10% of the mass of the nano-hydroxyapatite.

[0011] Furthermore, in step (2), the porogen is polyvinyl pyrrolidone and sodium chloride, and the mass ratio of the two is 1:0.1-0.3.

[0012] Furthermore, in step (2), the mass of the porogen is 20-60% of the mass of the bionic composite material.

[0013] Furthermore, the preparation method of the cross-linked network bio-based polyurethane in step (1) is carried out according to the following steps:

[0014] Step S1, under a nitrogen atmosphere, polyethylene glycol, olefinic cyclodextrin, and chitosan are added to a three-necked flask equipped with a mechanical stirrer, and after they are evenly mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 75-90° C. for 2-5 hours, cooled to 50-60° C., 2,2-dihydroxymethylpropionic acid is added, and the reaction is continued for 0.5-1 hour, triethylamine is added to adjust the pH to 7-8, and then L-cysteine ​​is added, and the mixture is stirred at 1000-1500 r / min for 20-40 minutes, concentrated and dialyzed at room temperature to obtain bio-based polyurethane.

[0015] Step S2: under nitrogen atmosphere, add bio-based polyurethane and methacrylated gelatin into a reaction flask, stir evenly, add a photoinitiator, initiate polymerization by ultraviolet light (wavelength of 365 nm) at a power of 10-20 W, and obtain a cross-linked network bio-based polyurethane.

[0016] Furthermore, in step S1, the mass ratio of polyethylene glycol, olefinic cyclodextrin, chitosan, isophorone diisocyanate, dibutyltin dilaurate, 2,2-dihydroxymethylpropionic acid, and L-cysteine ​​is 100:2-4:5-8:20-35:3-6:1.1-1.4:0.1-0.5.

[0017] Furthermore, in step S2, the initiator is any one of benzoyl peroxide, azobisisobutyronitrile or diisopropylbenzene peroxide.

[0018] Furthermore, in step S2, the mass ratio of bio-based polyurethane, methacrylated gelatin, and photoinitiator is 100:15-30:2-5.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention aims at the shortcomings of poor degradability and lack of biological activity of bio-based polyurethane constructed by the current chemical synthesis method. L-cysteine ​​has excellent biocompatibility and wound healing performance, chitosan and cyclodextrin with good biodegradability are used to participate in the polymerization of polyurethane, and L-cysteine ​​is added to end-cap the polyurethane. Then, the olefinic groups of cyclodextrin and modified gelatin in the polyurethane are used to initiate polymerization, and a stable and multifunctional cross-linked network bio-based polyurethane with controllable degradability is constructed through hydrogen bonds or covalent bonds. Then, the bio-based polyurethane is compounded with hydroxyapatite and subjected to pore formation to obtain a composite bone scaffold material for bone tissue repair, which plays a highly efficient therapeutic role in the bone tissue repair process.

[0021] The cross-linked network bio-based polyurethane has a dense three-dimensional network structure, and cyclodextrin, chitosan and gelatin are connected by chemical bonds, and there is a strong interaction; at the same time, because hydroxyapatite can produce hydrogen bonds and other chemical bonds with bio-based polyurethane, it is evenly distributed in the bio-based polyurethane substrate. When an external force acts, the rigid nanoparticles of the composite material become stress concentration points, and the polymer begins to produce local yielding, plastic deformation occurs and absorbs a large amount of impact energy. The appropriate pore size enables the composite material to play a buffering role when subjected to external force compression, thereby showing good compressive strength; therefore, the composite bone scaffold material prepared by the present invention has a three-dimensional porous network structure, which is more conducive to implantation into the human body to replace human bones for bone transplantation, and has a great promoting effect on bone ingrowth and the formation of new bones.

[0022] L-cysteine ​​is a sulfur-containing amino acid that can be converted into glutathione, which can remove free radicals in the body and reduce oxidative stress. Its therapeutic mechanism is to promote the production of H 2 S, then through H 2 S accelerates the polarization of macrophage subtypes to the M2 subtype to promote tissue repair and regeneration; at the same time, in bone scaffold materials, L-cysteine ​​can provide necessary nutritional support, promote cell proliferation and differentiation, and accelerate the tissue repair process. At the same time, it can also improve the local microenvironment, provide better conditions for cell growth and differentiation, avoid inflammatory and immune responses caused by bone implantation, and achieve the purpose of rapid treatment of bone defects to meet clinical needs. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Unless otherwise specified, the raw materials and reagents used in this application are commercially available or can be prepared by known methods.

[0025] The preparation method of allyl cyclodextrin is as follows: 1.135 g of β-cyclodextrin is dissolved in 60 mL of anhydrous N, N-dimethylformamide and anhydrous dimethyl sulfoxide of equal volume, 3.54 g of sodium hydroxide is added while stirring, the mixture is stirred at room temperature for 1 hour, the mixture is naturally cooled to 5-10°C, 8 mL of allyl bromide is added twice while stirring, the reaction is continued for 48 hours, after the reaction is completed, the mixture is allowed to stand for 2 hours, and the mixture is concentrated under reduced pressure. The residue is washed with acetone for several times, filtered and dried to obtain allyl cyclodextrin (structural formula: ).

[0026] Preparation of methacrylated gelatin: Dissolve 5 g of gelatin in 50 mL of PBS solution at 50°C, stir evenly at 300 rpm, add 3 mL of methacrylic anhydride, mix and stir for 1 hour, collect the product in a dialysis bag and dialyze it with deionized water at a constant temperature of 40°C for 3 days, and freeze-dry to obtain methacrylated gelatin.

[0027] Example 1

[0028] (1) Under nitrogen atmosphere, 100 g of polyethylene glycol, 3 g of olefinic cyclodextrin, and 6 g of chitosan were added to a three-necked flask equipped with a mechanical stirrer. After they were evenly mixed, 30 g of isophorone diisocyanate and 5 g of dibutyltin dilaurate were added, and the mixture was reacted at 85 °C for 4 h. The temperature was lowered to 55 °C, 1.3 g of 2,2-dihydroxymethylpropionic acid was added, and the reaction was continued for 0.5 h. Triethylamine was added to adjust the pH to 8, and then 0.1 g of L-cysteine ​​was added. The mixture was stirred at 1200 r / min for 30 min, concentrated and dialyzed at room temperature to obtain bio-based polyurethane.

[0029] (2) Under nitrogen atmosphere, 100 g of bio-based polyurethane and 25 g of methacrylated gelatin were added to a reaction flask. After stirring, 4 g of benzoyl peroxide was added and polymerization was initiated by ultraviolet light (wavelength of 365 nm) at a power of 15 W to obtain a cross-linked network bio-based polyurethane.

[0030] (3) Under a nitrogen atmosphere, 10 g of nano-hydroxyapatite and dimethyl sulfoxide were added to a reaction flask, stirred evenly, and then 0.2 g of a cross-linked network bio-based polyurethane was added. The mixture was reacted at 165 °C for 5 h, washed, filtered under reduced pressure, injected into a mold, maintained at 10 MPa for 8 min, and dried to obtain a bionic composite material.

[0031] (4) 10 g of biomimetic composite material, 0.2 g of porogen (the mass ratio of polyvinyl pyrrolidone to sodium chloride is 1:0.3) and ethanol were added to the reaction flask, ultrasonically oscillated, and reacted at 70 °C for 2 h. After the viscosity increased, the mixture was poured into a mold and dried at 60 °C for 18 h. After demolding, the mixture was cleaned by ultrasonic heating and dried to obtain a composite bone scaffold material for bone tissue repair.

[0032] Example 2

[0033] (1) Under nitrogen atmosphere, 100 g of polyethylene glycol, 2 g of olefinic cyclodextrin, and 5 g of chitosan were added to a three-necked flask equipped with a mechanical stirrer. After they were evenly mixed, 20 g of isophorone diisocyanate and 3 g of dibutyltin dilaurate were added, and the mixture was reacted at 90 °C for 2 h. The temperature was lowered to 60 °C, 1.1 g of 2,2-dihydroxymethylpropionic acid was added, and the reaction was continued for 1 h. Triethylamine was added to adjust the pH to 7, and then 0.1 g of L-cysteine ​​was added. The mixture was stirred at 1500 r / min for 20 min, concentrated and dialyzed at room temperature to obtain bio-based polyurethane.

[0034] (2) Under nitrogen atmosphere, 100 g of bio-based polyurethane and 15 g of methacrylated gelatin were added to a reaction flask. After stirring evenly, 2 g of azobisisobutyronitrile was added and polymerization was initiated by ultraviolet light (wavelength of 365 nm) at a power of 20 W to obtain a cross-linked network bio-based polyurethane.

[0035] (3) Under nitrogen atmosphere, 10 g of nano-hydroxyapatite and dimethyl sulfoxide were added to the reaction flask, and after stirring, 0.2 g of cross-linked network bio-based polyurethane was added, and the mixture was reacted at 175 °C for 3 h. The mixture was washed, filtered under reduced pressure, injected into a mold, maintained at 15 MPa for 5 min, and dried to obtain a bionic composite material.

[0036] (4) 10 g of biomimetic composite material, 0.3 g of porogen (the mass ratio of polyvinyl pyrrolidone to sodium chloride is 1:0.25) and ethanol were added to the reaction flask, ultrasonically oscillated, and reacted at 80 °C for 1 h. After the viscosity increased, the mixture was poured into a mold and dried at 65 °C for 16 h. After demolding, the mixture was cleaned by ultrasonic heating and dried to obtain a composite bone scaffold material for bone tissue repair.

[0037] Example 3

[0038] (1) Under nitrogen atmosphere, 100 g of polyethylene glycol, 4 g of olefinic cyclodextrin, and 8 g of chitosan were added to a three-necked flask equipped with a mechanical stirrer. After they were evenly mixed, 35 g of isophorone diisocyanate and 6 g of dibutyltin dilaurate were added, and the mixture was reacted at 75 °C for 5 h. The temperature was lowered to 50 °C, 1.4 g of 2,2-dihydroxymethylpropionic acid was added, and the reaction was continued for 1 h. Triethylamine was added to adjust the pH to 8, and then 0.1 g of L-cysteine ​​was added. The mixture was stirred at 1000 r / min for 40 min, concentrated and dialyzed at room temperature to obtain bio-based polyurethane.

[0039] (2) Under nitrogen atmosphere, 100 g of bio-based polyurethane and 30 g of methacrylated gelatin were added to a reaction flask. After stirring evenly, 5 g of diisopropylbenzene peroxide was added and polymerization was initiated by ultraviolet light (wavelength of 365 nm) at a power of 10 W to obtain a cross-linked network bio-based polyurethane.

[0040] (3) Under nitrogen atmosphere, 10 g of nano-hydroxyapatite and dimethyl sulfoxide were added to the reaction flask, and after stirring, 0.2 g of cross-linked network bio-based polyurethane was added, and the mixture was reacted at 150 °C for 8 h. The mixture was washed, filtered under reduced pressure, injected into a mold, maintained at 8 MPa for 10 min, and dried to obtain a bionic composite material.

[0041] (4) 10 g of biomimetic composite material, 0.4 g of porogen (the mass ratio of polyvinyl pyrrolidone to sodium chloride is 1:0.2) and ethanol were added to the reaction flask, ultrasonically oscillated, and reacted at 60 °C for 3 h. After the viscosity increased, the mixture was poured into a mold and dried at 50 °C for 24 h. After demolding, the mixture was cleaned by ultrasonic heating and dried to obtain a composite bone scaffold material for bone tissue repair.

[0042] Example 4

[0043] (1) Under nitrogen atmosphere, 100 g of polyethylene glycol, 2.5 g of olefinic cyclodextrin, and 6.5 g of chitosan were added to a three-necked flask equipped with a mechanical stirrer. After they were evenly mixed, 25 g of isophorone diisocyanate and 4.5 g of dibutyltin dilaurate were added, and the mixture was reacted at 80 °C for 4 h. The temperature was lowered to 60 °C, 1.2 g of 2,2-dihydroxymethylpropionic acid was added, and the reaction was continued for 1 h. Triethylamine was added to adjust the pH to 8, and then 0.1 g of L-cysteine ​​was added. The mixture was stirred at 1400 r / min for 35 min, concentrated and dialyzed at room temperature to obtain bio-based polyurethane.

[0044] (2) Under nitrogen atmosphere, 100 g of bio-based polyurethane and 25 g of methacrylated gelatin were added to a reaction flask. After stirring, 3 g of benzoyl peroxide was added and polymerization was initiated by ultraviolet light (wavelength of 365 nm) at a power of 18 W to obtain a cross-linked network bio-based polyurethane.

[0045] (3) Under a nitrogen atmosphere, 10 g of nano-hydroxyapatite and dimethyl sulfoxide were added to a reaction flask, stirred evenly, and then 0.2 g of a cross-linked network bio-based polyurethane was added. The mixture was reacted at 165 °C for 5 h, washed, filtered under reduced pressure, injected into a mold, maintained at 12 MPa for 9 min, and dried to obtain a bionic composite material.

[0046] (4) 10 g of biomimetic composite material, 0.5 g of porogen (the mass ratio of polyvinyl pyrrolidone to sodium chloride is 1:0.15) and ethanol are added to a reaction flask, ultrasonically oscillated, and reacted at 75 °C for 3 h. After the viscosity increases, the mixture is poured into a mold and dried at 60 °C for 20 h. After demolding, the mixture is cleaned by ultrasonic heating and dried to obtain a composite bone scaffold material for bone tissue repair.

[0047] Example 5

[0048] (1) Under nitrogen atmosphere, 100 g of polyethylene glycol, 4 g of olefinic cyclodextrin, and 7 g of chitosan were added to a three-necked flask equipped with a mechanical stirrer. After they were evenly mixed, 30 g of isophorone diisocyanate and 5 g of dibutyltin dilaurate were added, and the mixture was reacted at 80 °C for 5 h. The temperature was lowered to 50 °C, 1.4 g of 2,2-dihydroxymethylpropionic acid was added, and the reaction was continued for 1 h. Triethylamine was added to adjust the pH to 7, and then 0.1 g of L-cysteine ​​was added. The mixture was stirred at 1500 r / min for 30 min, concentrated and dialyzed at room temperature to obtain bio-based polyurethane.

[0049] (2) Under nitrogen atmosphere, 100 g of bio-based polyurethane and 28 g of methacrylated gelatin were added to a reaction flask. After stirring evenly, 5 g of azobisisobutyronitrile was added and polymerization was initiated by ultraviolet light (wavelength of 365 nm) at a power of 16 W to obtain a cross-linked network bio-based polyurethane.

[0050] (3) Under nitrogen atmosphere, 10 g of nano-hydroxyapatite and dimethyl sulfoxide were added to the reaction flask, and after stirring, 0.2 g of cross-linked network bio-based polyurethane was added, and the mixture was reacted at 160 °C for 8 h. The mixture was washed, filtered under reduced pressure, injected into a mold, maintained at 10 MPa for 6 min, and dried to obtain a bionic composite material.

[0051] (4) 10 g of biomimetic composite material, 0.6 g of porogen (the mass ratio of polyvinyl pyrrolidone to sodium chloride is 1:0.1) and ethanol were added to the reaction flask, ultrasonically oscillated, and reacted at 75 °C for 3 h. After the viscosity increased, the mixture was poured into a mold and dried at 55 °C for 24 h. After demolding, the mixture was cleaned by ultrasonic heating and dried to obtain a composite bone scaffold material for bone tissue repair.

[0052] Comparative Example 1

[0053] The difference between this comparative example and Example 1 is that no porogen is added in step (4), and other conditions remain the same.

[0054] Porosity test: Liquid replacement method was used to test. A certain volume of ethanol was measured and placed in a test tube. The prepared composite bone scaffold material was pressed into a block. Anhydrous ethanol was used as the replacement liquid. Each composite material was measured 3 times and the average value was taken. If the original volume of anhydrous ethanol in the test tube is V 0 , put the material in and wait for it to be completely soaked for a certain period of time, with no bubbles generated as the standard, and record the total volume of the composite material and anhydrous ethanol at this time as V 1 , volume difference V 1 -V 0 The volume of the composite material is represented by the contour volume, excluding the volume of the pores, and then the volume of the anhydrous ethanol remaining after removing the material is expressed as V 2 Indicates that the volume difference V 0-V 2 It represents the volume of anhydrous ethanol immersed in the composite material, that is, the volume of the material pores, V 1 -V 2 is the total volume of the composite material. 0 -V 2 ) / (V 1 -V 2 )×100%.

[0055] Mechanical property test: The prepared composite bone scaffold material is placed in a mold and pressed into tablets. A pressure of 11t is maintained for 5 minutes to form a thin sheet with a diameter of 13mm and a thickness of 2mm. A tablet four-purpose measuring instrument is used, and the sheet sample is placed between the probe and the test bench. Then the run button is pressed. When the sheet sample is squeezed and broken, the window displays the value of the hardness of the sample being tested, expressed in MPa.

[0056] Table 1 Porosity and compressive strength test

[0057] Porosity (%) Compressive strength(MPa) Example 1 45.5 8.0 Example 2 59.2 8.5 Example 3 71.3 8.7 Example 4 78.0 8.1 Example 5 81.4 7.7 Comparative Example 1 - 8.2

[0058] The porosity can provide a high surface area for cell-to-cell interaction for extracellular matrix regeneration, and sufficient space for convenient and smooth transportation of nutrients, blood, and nutrients; as can be seen from the test results in the above table, the porosity of the composite bone scaffold material increases with the increase of the porogen content and the increase of the mass percentage of polyvinyl pyrrolidone in the porogen, because on the one hand, the liquid-gas phase transfer of ethanol, when the sodium chloride particles are filtered out, the space originally occupied by the sodium chloride particles becomes a pore, which is connected with the gap formed by the overflow of ethanol gas, thereby forming a multi-level pore that is interconnected; on the other hand, polyvinyl pyrrolidone is a high molecular organic compound, its density is smaller than that of sodium chloride, and it has good compatibility with polyurethane, can be more evenly dispersed in the composite material, and can also play a certain mediating role, the two act synergistically to form mutually interconnected pores, the porosity in Example 3 is 71.3%, which is basically consistent with the pore requirement of cancellous bone of the human body, and is conducive to bone growth and nutrient transportation.

[0059] The cross-linked network bio-based polyurethane has a dense three-dimensional network structure, and cyclodextrin, chitosan and gelatin are connected by chemical bonds, and there is a strong interaction; at the same time, because hydroxyapatite can produce chemical bonds such as hydrogen bonds with bio-based polyurethane, it is evenly distributed in the bio-based polyurethane substrate. When an external force acts, the rigid nanoparticles of the composite material become stress concentration points, and the polymer begins to produce local yielding, plastic deformation occurs and absorbs a large amount of impact energy. The appropriate pore size makes the composite material play a buffering role when subjected to external force extrusion, thereby showing good compressive strength; but if the polyvinyl pyrrolidone content is too high, it will seriously hinder the internal rotation of the polyurethane molecular chain, the hydrogen bond action probability is reduced, and the mechanical properties are reduced. Therefore, the composite bone scaffold material prepared by the present invention has a three-dimensional porous mesh structure, which is more conducive to implanting the human body to replace human bones for bone transplantation, and has a great promoting effect on bone growth and the generation of new bones.

[0060] Example 6

[0061] The difference between this embodiment and embodiment 3 is that the content of L-cysteine ​​in step (1) is 0.2 g, the content of cross-linked network bio-based polyurethane in step (3) is 0.4 g, and other conditions remain the same.

[0062] Example 7

[0063] The difference between this embodiment and embodiment 3 is that the content of L-cysteine ​​in step (1) is 0.3 g, the content of cross-linked network bio-based polyurethane in step (3) is 0.6 g, and other conditions remain the same.

[0064] Example 8

[0065] The difference between this embodiment and embodiment 3 is that the content of L-cysteine ​​in step (1) is 0.4 g, the content of cross-linked network bio-based polyurethane in step (3) is 0.8 g, and other conditions remain the same.

[0066] Example 9

[0067] The difference between this embodiment and embodiment 3 is that the content of L-cysteine ​​in step (1) is 0.5 g, the content of cross-linked network bio-based polyurethane in step (3) is 1 g, and other conditions remain the same.

[0068] Comparative Example 2

[0069] The difference between this comparative example and Example 3 is that L-cysteine ​​is not added in step (1), and other conditions remain the same.

[0070] Comparative Example 3

[0071] The difference between this comparative example and Example 3 is that in step (4), nano-hydroxyapatite is used instead of the biomimetic composite material (ie, the biomimetic composite material is not added), and other conditions remain the same.

[0072] Antibacterial performance test: LB culture medium and physiological saline were prepared to revive the bacteria, and the bacterial solution was diluted with physiological saline to a concentration of 10 5 CFU / mL, weigh 50 mg of the prepared composite bone scaffold material, sterilize it with ultraviolet light, put it into a 50 mL conical flask, add 1 mL of LB culture medium, and add 0.2 mL of bacterial solution (Escherichia coli and Staphylococcus aureus), and co-culture the sample and bacterial solution at 37 ° C in a shaker at 120 rpm for 14 days, take 100 μL of the mixed solution and inoculate the plate by the culture medium pouring method, place the culture plate in a 37 ° C bacterial incubator for 24 hours, calculate the number of colonies, and calculate the inhibition rate.

[0073] Table 2 Antibacterial rate test

[0074]

[0075] From the test results in the above table, it can be seen that with the increase of L-cysteine ​​and cross-linked bio-based polyurethane content, the antibacterial rate of the composite bone scaffold material gradually increases. In Example 9, the antibacterial rates of Escherichia coli and Staphylococcus aureus reached 99.9% and 97.2%, respectively. This is because L-cysteine ​​is a sulfur-containing amino acid that can be converted into glutathione, which is a powerful antioxidant that can remove free radicals in the body and reduce oxidative stress. Its therapeutic mechanism is to promote the production of H 2 S, then through H 2 S accelerates the polarization of macrophage subtypes to the M2 subtype to promote tissue repair and regeneration; at the same time, in bone scaffold materials, L-cysteine ​​can provide necessary nutritional support, promote cell proliferation and differentiation, accelerate the tissue repair process, and it can also improve the local microenvironment and provide better conditions for cell growth and differentiation.

[0076] In vitro degradation performance test: The prepared composite scaffold material was cut into 1cm×1cm×1cm cubes, and then the samples were immersed in simulated body fluids and placed in a shaker at 37°C with the speed set to 120rpm. Samples were taken on 14 days, dried to constant weight, and weighed, and the degradation rate was calculated. Degradation rate = (mass before degradation - sample mass after degradation) / mass before degradation × 100%.

[0077] Table 3 Degradation rate test

[0078] Degradation rate (%) Example 3 29.6 Example 6 30.1 Example 7 32.3 Example 8 33.7 Example 9 35.8 Comparative Example 2 27.3 Comparative Example 3 12.5

[0079] The above-mentioned embodiments merely express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a composite bone scaffold material for bone tissue repair, characterized in that: The preparation method is carried out according to the following steps: Step (1), under a nitrogen atmosphere, adding nano-hydroxyapatite and dimethyl sulfoxide to a reaction flask, stirring evenly, adding cross-linked network bio-based polyurethane, reacting at 150-175° C. for 3-8 hours, washing, vacuum filtering, injecting into a mold, maintaining at 8-15 MPa for 5-10 minutes, and drying to obtain a bionic composite material; Step (2), adding the bionic composite material, porogen and ethanol into the reaction flask, ultrasonically oscillating, reacting at 60-80°C for 1-3h, pouring into a mold after the viscosity increases, applying pressure at 50-65°C and drying for 16-24h, demolding, cleaning by ultrasonic heating, and drying to obtain a composite bone scaffold material for bone tissue repair.

2. The method for preparing the composite bone scaffold material for bone tissue repair according to claim 1, characterized in that: The mass of the cross-linked network bio-based polyurethane in step (1) is 2-10% of the mass of the nano-hydroxyapatite.

3. The method for preparing the composite bone scaffold material for bone tissue repair according to claim 1, characterized in that: In the step (2), the porogen is polyvinyl pyrrolidone and sodium chloride, and the mass ratio of the two is 1:0.1-0.

3.

4. The method for preparing a composite bone scaffold material for bone tissue repair according to claim 1, characterized in that: The mass of the porogen in step (2) is 20-60% of the mass of the bionic composite material.

5. The method for preparing the composite bone scaffold material for bone tissue repair according to claim 1, characterized in that: The method for preparing the cross-linked network bio-based polyurethane in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, polyethylene glycol, olefinic cyclodextrin, and chitosan are added to a three-necked flask equipped with a mechanical stirrer, and after they are evenly mixed, isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 75-90° C. for 2-5 hours, cooled to 50-60° C., 2,2-dihydroxymethylpropionic acid is added, and the reaction is continued for 0.5-1 hour, triethylamine is added to adjust the pH to 7-8, and then L-cysteine ​​is added, and the mixture is stirred at 1000-1500 r / min for 20-40 minutes, concentrated and dialyzed at room temperature to obtain bio-based polyurethane; Step S2: under nitrogen atmosphere, add bio-based polyurethane and methacrylated gelatin into a reaction flask, stir evenly, add a photoinitiator, initiate polymerization by ultraviolet light at a power of 10-20 W, and the wavelength of the ultraviolet light is 365 nm to obtain a cross-linked network bio-based polyurethane.

6. The method for preparing the composite bone scaffold material for bone tissue repair according to claim 5, characterized in that: In the step S1, the mass ratio of polyethylene glycol, olefinic cyclodextrin, chitosan, isophorone diisocyanate, dibutyltin dilaurate, 2,2-dihydroxymethylpropionic acid, and L-cysteine ​​is 100:2-4:5-8:20-35:3-6:1.1-1.4:0.1-0.

5.

7. The method for preparing the composite bone scaffold material for bone tissue repair according to claim 5, characterized in that: In step S2, the initiator is any one of benzoyl peroxide, azobisisobutyronitrile or dicumyl peroxide.

8. The method for preparing the composite bone scaffold material for bone tissue repair according to claim 5, characterized in that: In the step S2, the mass ratio of the bio-based polyurethane, methacrylated gelatin and the photoinitiator is 100:15-30:2-5.

9. A composite bone scaffold material for bone tissue repair, characterized in that: Obtained by the preparation method according to any one of claims 1 to 8.